Market Making with Discrete Prices - Anshuman, V. Ravi; Kalay, Avner (Review of Financial Studies, 1998)
[Exchange-mandated discrete pricing restrictions create a wedge between the underlying equilibrium price and the observed price. This wedge permits a competitive market maker to realize economic profits that could help recoup fixed costs. The optimal tick size that maximizes the expected profits of the market maker can be equal to $1/8 for reasonable parameter values. The optimal tick size is decreasing in the degree of adverse selection. Discreteness per se can cause time-varying bid-ask spreads, asymmetric commissions, and market breakdowns. Discreteness, which imposes additional transaction costs, reduces the value of private information. Liquidity traders can benefit under certain conditions.]